نمودهای فمینیستى در سروده "اینک دختری میهن من است" - رهشيد, جيهاد شوكرى (Sulaimani Journal for Humanities, 2021)
One of the places of occurring of feminism group in the world, the literary area of any nationality which in Kurdish literature this area wasn't effectiveness and the trace of this group is clear in the poetry of Kurdish poets who they are alive witnesses of this method. Sherko Bekas is one of the famous Kurdish poets who innovated a new technique in expressing his own opinion and view in his poems, and that is why some people are still fond of his poems. Sherko's views in his poem (Now a Girl is my Patriot) show the poet's deep believe in raising woman's degree and he left this forgotten method and an obvious horizon for his new generation. This research wants to elucidate and analyze his concepts after reading his poems, and analyzing the most important characteristics of the poetry's feminist structure that can be found in the poems of this poet. In short, this research will clarify Sherko's relation with European's society and culture, and observing the difference between women's knowledge and the most important aspects of building a feminism method, and that he could set up his own community.